Design and Development Smart Inhaler System - Mai Noor Asiah Bt Tan Zalilah; Ab Rahman, Putri Irda (J-Innovation, 2025)
The prevalence of respiratory diseases, such as asthma and Chronic Obstructive Pulmonary Disease (COPD), continues to increase worldwide, posing significant challenges for patients and healthcare systems. Monitoring remaining doses and inhaler dose notifications are becoming increasingly scarce, becoming a major concern for asthma patients. Therefore, the Smart Inhaler is designed to provide a real-time shrinking dose counter display and notifications via devices for refilling inhaler doses. This Smart Inhaler consists of a 3.7V power supply and Force Resistive Sensor used as input, display on OLED notifications as output, and ESP32 as a processor to connect to the Internet. The Smart Inhaler uses an IoT application as a counter that connects the inhaler to devices such as smartphones. Force Resistive Sensor is used to determine the dose taken by the user, and calculations are subtracted until the inhaler dose is depleted. Notifications are sent to the device when the Smart Inhaler reaches a low dose count, starting from 50,30 to 10 doses, to remind patients to replace the inhaler. This Smart Inhaler can be enhanced with a more practical design on the top of the metal canister to facilitate inhaler dose calculation by the Force Resistive Sensor.